Letters from Kathmandu : the Kot Massacre - Stiller, Ludwig F. (Research Centre for Nepal and Asian Studies, Tribhuvan University, Kiritipur, 1981)
On the 1846 massacre in Kathmandu marking the beginning of Rana rule in Nepal.